Self-assembled hyaluronate/protamine polyelectrolyte nanoplexes: synthesis, stability, biocompatibility and potential use as peptide carriers - TAJBER, LIDIA; SANTOS-MARTINEZ, MARIA; MEDINA MARTIN, CARLOS; CORRIGAN, OWEN (My University, 2014)
This work investigates a new type of polyelectrolyte complex nanocarrier composed of hyaluronic acid (HA) and protamine (PROT). Small (approximately 60 nm) and negatively charged nanoparticles (NPs) with a polydispersity index of less than 0.2 were obtained with properties that were dependent on the mixing ratio, concentration of polyelectrolytes and molecular weight of HA. Salmon calcitonin (sCT) was efficiently (up to 100%) associated with the NPs, and the drug loading (9.6-39% w/w) was notably high, possibly due to an interaction between HA and sCT. The NPs released -70-80% of the sCT after 24 hours, with the estimated total amount of released sCT depending on the amount of HA and PROT present in the NPs. The isoelectric point of the NPs was close to pH 2, and the negative surface charge was maintained above this pH. The HA/PROT nanoplexes protected the sCT from enzymatic degradation and showed low toxicity to intestinal epithelial cells, and thus may be a promising oral delivery system for peptides.
PUBLISHED
Keywords: Immunology, Inflammation & Infection; Nanoscience & Materials; Biomedical applications of nanotechnology; DRUG DELIVERY SYSTEMS; Nanotechnology; Pharmacy